ASSESSMENT OF PARACHOLOROMETACRESOL (PCMC), A FUNGICIDE AGAINST THREE COMMON FUNGAL SPECIES IN LEATHER MANUFACTURING - J.RAVINDRAN,; N. RAJESWARI, (International Journal of Pharma and Bio Sciences, 2016)
Raw hide is the most susceptible substrate for the attack of microorganisms. The microbial attack is high in the vegetable tanned leather than the chrome tanned leather. The present study is designed to isolate, standardize, study and to perform application studies on the antifungal efficacy of PCMC on the isolated fungal species from vegetable tanned leather. The three isolated fungal species such as Aspergillus niger, Aspergillus flavus and Trichophyton rubrum were presently used for the study. Antifungal susceptibility and physical characteristics of leather was tested and the minimum inhibitory concentration (MIC) of PCMC against Aspergillus niger and Aspergillus flavus was found to be 80 µl, whereas against Trichophyton rubrum was found to be 40 µl. Application study conducted showed that 0.1% of PCMC is sufficient to control the growth of isolated fungal species on leather. The physical properties of leather showed moderate deterioration on fungal attack. All these studies were performed indicate that PCMC was found to be effective in protecting leather against attack by all these three isolated species. Aspergillus niger, Aspergillus Flavus, Trichophyton rubrum, fungicide, leather manufacturing.